Awareness of gestational diabetes mellitus and its associated factors among pregnant women in public hospitals in the East Gojjam Zone, Northwest Ethiopia: a cross-sectional study - Mihiret, Getachew Tilaye; Solomon Wondmu, Kumlachew; Baye, Fekadu; Minale, Mulunesh; Yechale, Mastewal; Fikrie Melese, Misganaw; Haimanot, Aysheshim Belaineh; Getaneh, Temesgen (Frontiers in Global Women's Health, 2025)
BackgroundGestational diabetes mellitus (GDM) is the most common metabolic complication during pregnancy and is associated with an increased risk of maternal and neonatal adverse outcomes. Despite it being the most prevalent complication and leading to poor pregnancy outcomes, there have been very few studies assessing awareness of GDM among pregnant women in Ethiopia. Therefore, this study aimed to determine the awareness of GDM and its associated factors among pregnant women in public hospitals in the East Gojjam Zone, Northwest Ethiopia.MethodsAn institution-based cross-sectional study was conducted from June to August 2024. A systematic random sampling technique was utilized to select 423 participants. The data were collected using an interviewer-administered questionnaire. The collected data were analyzed using SPSS version 25. Binary logistic regression was fitted to assess the association between the explanatory variables and the outcome variable. Variables with a p-value less than 0.05, along with corresponding 95% confidence intervals, were used to declare statistical significance.ResultsThis study found that 27.0% (95% CI: 0.23–0.31) of the pregnant women were aware of GDM. The most common source of information about GDM was friends at 53.2%, followed by family and healthcare professionals. Factors such as partner involvement [adjusted odds ratio (AOR) = 0.58; 95% CI = (0.35–0.95)], family history of chronic medical conditions [AOR = 5.20; 95% CI = (2.40–11.25)], mistimed but wanted pregnancies [AOR = 3.36; 95% CI = (1.40–8.10)], and being Muslim [AOR = 2.89; 95% CI = (1.34–6.24)] were significantly associated with awareness of GDM.ConclusionOnly a small proportion of pregnant women were aware of GDM. Mistimed but desired pregnancies, partner involvement, and family history of chronic medical conditions were significantly associated with GDM awareness. In order to mitigate the growing burden of GDM, healthcare professionals need to do more to educate women about GDM during their prenatal care follow-ups.